Efficacy of urgent colonoscopy for colonic diverticular bleeding: A propensity score‐matched analysis using a nationwide database in Japan. Issue 6 (20th November 2020) - Moroi, Rintaro; Tarasawa, Kunio; Shiga, Hisashi; Yano, Kota; Shimoyama, Yusuke; Kuroha, Masatake; Kakuta, Yoichi; Fushimi, Kiyohide; Fujimori, Kenji; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Background and Aim: Although colonic diverticular bleeding (CDB) is considered to have good prognosis with conservative therapy, some cases are severe. The efficacy of urgent colonoscopy for CDB and clinical factors affecting CDB prognosis are unclear. This study aimed to evaluate the efficacy of urgent colonoscopy for CDB and identify risk factors for unfavorable events, including in‐hospital death during admission, owing to CDB. Methods: We collected CDB patients' data using the Diagnosis Procedure Combination database system. We divided eligible patients into urgent and elective colonoscopy groups using propensity score matching and compared endoscopic hemostasis and in‐hospital death rates and length of hospital stay. We also conducted logistic regression analysis to identify clinical factors affecting CBD clinical events, including in‐hospital death, a relatively rare CDB complication. Results: Urgent colonoscopy reduced the in‐hospital death rate (0.35% vs 0.58%, P = 0.033) and increased the endoscopic hemostasis rate (3.0% vs 1.7%, P < 0.0001) compared with elective colonoscopy. Length of hospitalization was shorter in the urgent than in the elective colonoscopy group (8 vs 9 days, P < 0.0001). Multivariate analysis also revealed that urgent colonoscopy reduced in‐hospital death (odds ratio = 0.67, 95% confidence interval: 0.46–0.97, P = 0.036) and increased endoscopic hemostasis (odds ratio = 1.84, 95% confidence interval: 1.53–2.22, P < 0.0001). Conclusion: Urgent colonoscopy for CDB may facilitate identification of the bleeding site and reduce in‐hospital death. The necessity and appropriate timing of urgent colonoscopy should be considered based on patients' condition.